APPROACHING TO THE EUROPEAN MODEL OF ALCOHOL CONSUMPTION ON BASE OF LOWERING RISKS OF UKRAINIAN CONSUMERS AT WINE MARKET - A. Starostina; V. Kravchenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Development of theoretical principles of conception of the perceived risk is considered. Methodology of marketing research of the perceived risks at the market of dry wine of Kyiv is shown. Searching questions, hypotheses, methods of statistical verification of hypotheses of marketing research are shown. Estimation of dry wine customers of separate components of the perceived risk and strategies of their decline are described. Concrete directions of the development of market strategy and marketing-mix, which take into account the estimation of the perceived risks and strategies of their diminishing, are offered.